ÃÂÃÂÃÂ ÃËÃÂ£Ãâ¡Ãâ¦ "ÃÂ#$%& ÃÂ§ "()& ÃÂ§ "*+, THE POSITION AND IMPORTANCE OF ARABIC LANGUAGE - Ahmad Hasyim, Mohammad Yusuf (Language Circle: Journal of Language and Literature, 2011)
Arabic language is one of the United Nations language. It is a language which is used for thecitizen of Arabic peninsula, especially Arabian Gulf countries as oil producers. Arabic languageis the most important language which gets the highest position in Islam for the Moslemspeaker from Arabic or non Arabic countries since law of Islam, which are the Koran and thehadits, uses Arabic language. For centuries, the experts and proponents of Arabic languagehave been raising problems related to the position and importance of Arabic language in thework. Those problems nowadays are still current to be discussed or analyzed. How theposition and importance of Arabic language for Moslem or nonmoslem people, Arabian or nonArabian people is used and how the steps which is probably taken by non Arabian peopleaims to learn Arabic language well as religion language and international communicationlanguage are reached in this analysis.